Response of low-cost environmental monitors to typical emission events in daycare centers - Zheng, Hailin; Loomans, Marcel; Walker, Shalika; Zeiler, Wim (CLIMA 2022 conference, 2022)
Daycare centers (DCCs), the first program for the social development of young children (0-5 years old), are the most important place for young children besides their homes. Continuous indoor air quality (IAQ) monitoring in DCCs is a means to assess the IAQ and assure a healthy and comfortable environment for infants and toddlers. To date, an extensive array of low-cost air quality monitors (LCMs) is available on the commercial market. Still, only a limited number of these LCMs have been subjected to any research-based evaluation. Furthermore, performance evaluations of low-cost sensors in previous literature are mainly focused on residential emission activities. To the best of our knowledge, there is no research into simulating emission sources related to DCCs scenarios yet. Therefore, this study is aimed to evaluate the response of one type of LCM (2 units) to typical emissions events related to DCCs in detecting the IAQ parameters, that is, particulate matter (PM2.5, PM10), carbon dioxide (CO2), total volatile organic compounds (TVOC), temperature (T), and relative humidity (RH). The LCMs were compared to outcomes from research-grade instruments (RGIs). All the experiments were performed in a climate chamber, where 3 kinds of typical activities (Background test; Arts-and-crafts events; Cleaning events; in a total of 20 events) were simulated by recruited subjects in an indoor climate condition (cool and dry [20±1 ℃ & 40±5% ℃]). The IAQ parameters sensed by the LCM detected the majority of events, despite a difference in the magnitude of responses. Intra-sensor consistency was significantly strong for all IAQ parameters, with a mean coefficient of variation of 4.14%. The LCM particle sensor underestimated the reference concentrations, with a mean RMSE of 12.8 μg/m³ for PM2.5 and 36.5 μg/m³ for PM10. Although TVOC and CO2 sensors reported a weak quantitative response, both had a close correlation with RGIs’ data, with R2 values in the range of 0.8-1.0 and 0.5-1.0, respectively. A good qualitative and quantitative agreement was observed in both T (within 1.1°C) and RH sensor (within 1%). In summary, this study reveals that the LCMs investigated are useful in providing IAQ-based monitoring in the specific application scenarios of daycare centers.